Electron beam irradiation of ENR-50/PVC/CNTs nanocomposites: effect of sonication - Ahmad, Mohd. Shahrulnizam (2015)
The effect of sonication on the properties of electron beam (EB) irradiated Epoxidised Natural Rubber 50/Polyvinyl Chloride/Carbon Nanotubes (ENR-50/PVC/CNTs) nanocomposites were investigated. CNTs was dissolved and dispersed in 1000 mL of Dioctyl Phthalate (DOP) by using sonication. Sonication time were varied from 1 to 3 hours. The premixed PVC/MWNTs blend was prepared by premixing the sonicated CNT with PVC in a high speed dry mixer. Melt blending of premixed PVC/CNTs and ENR 50 was done in a Brabender Plastigraph at 150°C for 10 minutes. ENR-50/PVC/CNTs nanocomposites prepared from dry blended CNTs with PVC without sonication was used as control. The samples were irradiated by using electron beam with 2 MeV electron beam machine in a dose range of 50 to 200 kGy. The gel content, tensile properties and morphology properties of the ENR-50/PVC/CNTs nanocomposites were investigated as a function of sonication time and irradiation dose. The gel fraction and tensile properties of the ENR-50/PVC/CNTs prepared from sonication of CNTs in the presence of DOP found to have a lower values than control. Evidences from TEM analysis, indicated a more uniform dispersion of CNTs in PVC/ENR matrix is achieved prior to sonication of CNTs in the presence of DOP.